Legal Protection of Vaccine Administration Health Service to Prevent the Spread of the Coronavirus Disease 2019 in Indonesia - Budiono, Arief; Iriani, Dewi; Safira, Martha Eri; Roihanah, Rif’ah; Noor, Muhamad; Khasanah, Neneng Uswatun; Ridwan, Ridwan (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The increase of Coronavirus disease (COVID-19) infections leads countries to implement preventive steps such as wearing masks, social distancing, and vaccine administration. Indonesia started administering mass vaccination in January 2021 using the Sinovac vaccine, but there are still problems such as the emergence of side effects. AIM: This research aims to explain the legal protection of COVID-19 vaccine administration and its obstacles. METHODS: This is a normative legal study that uses library research. It uses the statute approach. RESULTS: The research results show that the legal protection of COVID-19 vaccine administration includes Law No. 36 of 2009 on Health and Presidential Decree No. 99 of 2020 on Vaccine Procurement and Administration to Overcome the COVID-19 Pandemic. Then, the obstacles in the vaccine administration include the limited stock of vaccines and supporting health equipment such as hazmat suits and injection needles. CONCLUSION: Thus, the government of Indonesia should implement the Health Protocols during this pandemic, as stipulated in the Decree of the Republic of Indonesia’s Ministry of Health No. Hk.01.07/Menkes/382/2020.